The purpose of this article is to elaborate denominal nominalsin Toba Batak language from the view point of generative transformational study. Denominal Nominals in Toba Batak: A Generative Transformational Study (The Explora, 2020)
The purpose of this article is to elaborate denominal nominalsin Toba Batak language from the view point of generative transformational study. The theory applied in this study is modified theory of Halle‟s model. Therefore, there are six components of sets of generative transformational rules as modified theory in this study, i.e. List of Morphemes, Word Formation Rules, Filter, Orthographic Rules, Phonological Rules, and Dictionary. The data were analysedby applying modified theory with reference to Halle‟s theory as the main theory. The method of this study is descriptive qualitative. The data were collected by using observation and interview. The collected data are voice-recordings and writings. The research findings show that denominalnominals in Toba Batak language are done by attaching (1) prefix [par-], (2) prefix [sa-], (3) infix [-ar-], (4) confix [ha-an], (5) confix[par-an], (6) and affix combination [pasi-]. The resultof the affixation processes generate complex words which have new grammatical and lexical meanings. Phoneme addition takes place in morphological process particularly with prefix [sa-]. The inflectional processes of attaching those affixes bring about phonologicalidiosincracy, therefore, such words must be processed in filter to generate acceptable words in Toba Bataklanguage.